A Preexperimental Study to Assess the Impact of an Interdisciplinary Educational Intervention on Nurses’ Knowledge of Perinatal and Infant Oral Health Care - Olatosi, Olubukola O. (J Int Soc Prev Community Dent, 2019)
OBJECTIVE: The objective of this study was to assess the impact of an interdisciplinary educational intervention on the knowledge of nursing practitioners regarding perinatal and infant oral health (PIOH) care. MATERIALS AND METHODS: This was a preexperimental study conducted among nursing practitioners in Lagos, Nigeria. Participants received hands-on training and didactic lectures, which included dental caries etiology and risk factors; oral hygiene and dietary education; teething and its management; dental trauma and its prevention; nonnutritive habits; screening, referrals, and counseling; and fluoride varnish application. Knowledge of the trainees was assessed using pre- and posttest questionnaires. Level of statistical significance was set at P < 0.05. RESULTS: Overall, 110 nurses participated in the study with a mean age of 40.9 ± 10.8 years; 106 (96.4%) were females. Approximately 88% of the participants had not received formal training on PIOH. The baseline mean scores of the participants’ knowledge on oral hygiene, teething, trauma, caries, and oral habits were 4.31 ± 1.9, 9.84 ± 2.6, 2.59 ± 1.7, 4.24 ± 1.8, and 1.45 ± 0.6, respectively; this increased significantly (P < 0.001) following the educational intervention with posttest mean scores as 7.58 ± 0.8, 11.79 ± 1.3, 4.34 ± 1.9, 6.19 ± 1.8, and 1.82 ± 0.4 and six-month evaluation scores as 6.21 ± 1.8,7 10.27 ± 3.1, 4.39 ± 1.5, 5.91 ± 1.8, and 1.79 ± 0.5, respectively. Overall posttest (31.4 ± 4.2) and six-month (28.6 ± 6.2) knowledge scores were significantly higher than the pretest values (22.4 ± 4.8, P < 0.001). At the six-month post-intervention survey, 84% of the nurses reported inclusion of PIOH education in their routine general health education sessions. CONCLUSION: There was a positive impact of the educational intervention as evidenced by an increase in the knowledge of the nurses on PIOH care and the inclusion of PIOH education in their general health education. A slight decline between posttest and six-month evaluation scores indicates a need for continuous education and evaluation.